A Hybrid Approach of Mathematical Optimization for Multi-Objective Model of Islamic Banking - Karmila Hanim Kamil; Shahida Shahimi; Abd. Ghafar Ismail; Zaidi Isa (Penerbit UTM Press, 2024)
Indexed by WOS/MyCite